A study of the functions and programs of the University Elementary School and its implications for Bansomdej Demonstration School - Bamroong, Parnsoonthorn (s.n.], 1971)
This study aimed at finding out how a laboratory school like Bansomdej Demonstration School can derive implications from an institutional analysis of the University Elementary School. The normative survey method was used. Documentary analysis was undertaken including fieldwork, which is a combination of direct observation and interviewing.